Unemployment benefit reforms to support employment and inclusiveness in the United States Impacts of the Pandemic Unemployment Assistance - Pearsall, Eliza-Jane (OECD Social, Employment and Migration Working Papers, 2023)
This paper analyses the impact of Pandemic Unemployment Assistance (PUA) extensions on jobseeker households in selected US states and examines how these extensions compare to the pre-pandemic policies. The analysis finds that PUA extensions increase benefit duration for all jobseekers, but due to interactions between other government benefits, this translates to significant increases in benefit generosity only for jobseekers without children. This has an impact on the financial incentives to take up employment, although incentives are still above the OECD average. PUA extensions have little impact for people who have been unemployed for a very long time, and jobseekers with no recent contribution history. PUA extensions also have minimal impact on jobless families with children who continue to receive less support compared to other OECD countries